(untitled) (CIPEEX, 2025)
The importance of studying the mental health of university professors is essential, as the prevalence of anxiety and depression among these professionals directly influences the teaching and learning process. The objective of this study was to review the literature on the prevalence of anxiety and depression among university professors and to investigate the factors that contribute to these conditions. This is an integrative literature review on the prevalence of anxiety and depression among university professors. The descriptors “anxiety,” “depression,” “professors,” and “university” were used in databases such as the Virtual Health Library (BVS) and Google Scholar. Publications from the last five years were reviewed, and only full-text articles available in English and Portuguese were included. Publications that, although they included the descriptors, did not directly address the objective were excluded. The advanced search using the descriptors resulted in 10 articles; after screening, 6 articles were excluded based on title and abstract review. After these analyses, a total of 4 articles were selected for the study. The findings indicate that university faculty face daily pressures, with many demands that lead to excessive worry, including the constant need for updating in the teaching and learning process. These factors have been associated with an increase in anxiety and depression rates among professors. Additionally, the exhausting workload, physical and mental burnout, and job security concerns further aggravate this situation. It is essential that higher education institutions recognize the importance of creating a work environment that integrates support projects for these professionals, aiming to develop action plans to improve the mental health of professors.